PROMOSI KESELAMATAN DAN KESEHATAN PSIKOSOSIAL DI UPT SMA NEGERI 30 BONE MELALUI PROGRAM ANTI BULLYING BERBASIS EDUKASI PARTISIPATIF BERKELANJUTAN UNTUK MEWUJUDKAN LINGKUNGAN AMAN - Andi Yepita Deviyanti; Hardianty Hardianty; Sitti Nurmanis Sari; Sri Rahayu Suparman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Bullying in schools is a serious threat to adolescents' psychosocial safety and well-being. At UPT SMA Negeri 30 Bone, verbal bullying is often normalized as harmless joking, while bystanders tend to hesitate to report bullying incidents, creating an unsafe learning environment. This community service program aimed to improve students' knowledge of psychosocial safety and health through a Sustainable Participatory Anti-Bullying Education Program. The program employed a Sustainable Participatory Education approach consisting of coordination with the school, pre-test assessment, interactive educational seminars, group discussions, and post-test evaluation. The results demonstrated a substantial improvement in students' knowledge, with the proportion of students categorized as having good knowledge increasing from 3 students (20%) during the pre-test to 14 students (93.3%) after the intervention. In addition, students showed greater willingness to express their opinions, discuss bullying prevention, and commit to creating a safer and more respectful school environment. These findings indicate that the Sustainable Participatory Education Program is effective in improving students' knowledge and awareness of bullying prevention while supporting the development of a safe and psychosocially healthy school environment.Keywords: Anti-bullying, Participatory Education; Psychosocial Health, Bullying, Senior High School Students.